CLINICAL FEATURES OF THE COURSE OF GOUT (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
To identify the frequency and nature of clinical and laboratory signs of metabolic syndrome in patients with gout. 49 male gout patients were examined in the rheumatology department. Thus, the acute variant of gouty arthritis was noted in 42.9%, prolonged – in 22.4% and chronic – in 34.7% of patients. Tofuses were found in 26.5% of patients. Very often, the comorbid course of gout and metabolic syndrome is due to a hereditary predisposition, the methods of prevention of which in gout can be the preservation of motor activity, dietary correction of body weight, as well as timely basic treatment.